Student voice in higher education diversity policies: A systematic review - Resch, Katharina (Frontiers in Education, 2023)
Diversity is considered central to the capacity of higher education institutions to thrive in an increasingly diverse society. Accordingly, diversity policies are developed and initiated to benefit students from diverse backgrounds. However, little is known about how students themselves assess these diversity policies (student voice). The systematic review described in this paper hence seeks to provide an overview of empirical evidence on student voice of diversity policies in higher education, looking thereby at corresponding studies published between 2000 and 2020. Of the 1,090 studies identified in the screening process, 21 were included in the final analysis. Two thematic strands emerged in the thematic analysis: diversity policies aiming at opening access to higher education and the representation of student voice. The review concludes with specific policy and research recommendations in this field.